PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2013-2015) - Anggit Tri Retnoningtyas; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2017)
Indicators of good working capital management is the efficiency of working capital. The components of working capital are turnover of cash, turnover of account receivables, turnover of inventories, and turnover of account payables. The main aim of this study is to analyze the effect of working capital management on firm’s  profitability. The object of this study is manufacturing companies basic industry and chemical sector which are listed at  Indonesian Stock Exchange (BEI) in the period 2013 to 2015. The study further reveals that turnover of cash, turnover of account receivables, turnover of inventories have a positive and significant effect on firm’s profitability, while turnover of account payables has no effect on the firm’s profitability.